[tex]\dfrac{h-w}{8}=m\ \ \ \ |\cdot8\\\\h-w=8m\ \ \ \ |-h\\\\-w=-h+8m\ \ \ |\text{change the signs}\\\\\boxed{w=h-8m}\\--------------------------\\h-\dfrac{w}{8}=m\ \ \ \ |-h\\\\-\dfrac{w}{8}=-h+m\ \ \ \ |\cdot(-8)\\\\\boxed{w=8h-8m}[/tex]
Can you help me find the side??? It's trigonometry!!
Answer: 5.6
===================================
Work Shown:
cos(angle) = adjacent/hypotenuse
cos(B) = AB/BC
cos(62) = AB/12
12*cos(62) = AB
AB = 12*cos(62)
AB = 5.63365875
AB = 5.6
7 1/8 is equal to greater than or less than 7.025
which expression is equivalent to the expression below? (m+3/m^2-16)/(m^2-9/m+4)
Answer:
B. 1/(m-4)(m-3)
Answer:
[tex]\frac{1}{(m-3)(m-4)}[/tex]
Step-by-step explanation:
(m+3/m^2-16)/(m^2-9/m+4)
Lets factor the numerator and denominator
use identity a^2 - b^2 = (a+b)(a-b)
[tex]m^2 - 16= m^2 - 4^2 = (m+4)(m-4)[/tex]
[tex]m^2 - 9= m^2 - 3^2 = (m+3)(m-3)[/tex]
we have divisiion sign in between, change the division symbol in to multiplication symbol by flipping the fraction in the denominator
(m+3/m^2-16)*(m+4/m^2-9)
[tex]\frac{m+3}{(m+4)(m-4)} * \frac{m+4}{(m+3)(m-3)}[/tex]
Cancel put m+3 and m+4 at the top and botom
[tex]\frac{1}{(m-3)(m-4)}[/tex]
Which expression is equal to 7/√5?
7√5/25
35√5
49/√35
7√5/5
[tex]Solution, \frac{7}{\sqrt{5}}=\frac{7\sqrt{5}}{5}\quad \left(\mathrm{Decimal:\quad }\:3.13050\dots \right)[/tex]
Answer Choice A. [tex]7\cdot \frac{\sqrt{5}}{25}=\frac{7\sqrt{5}}{25}\quad \left(\mathrm{Decimal:\quad }\:0.62610\dots \right)[/tex]
Answer Choice B. [tex]35\sqrt{5}=78.26238\dots[/tex]
Answer Choice C. [tex]\frac{49}{\sqrt{35}}=\frac{7\sqrt{35}}{5}\quad \left(\mathrm{Decimal:\quad }\:8.28251\dots \right)[/tex]
Answer Choice D. [tex]7\cdot \frac{\sqrt{5}}{5}=\frac{7\sqrt{5}}{5}\quad \left(\mathrm{Decimal:\quad }\:3.13050\dots \right)[/tex]
The correct answer is D. 7√5/5
Hope This Helps!!!
The expression that is equal to the equation 7/√5 is 7√5/5. The fourth option is correct.
[tex]\mathbf{\dfrac{7}{\sqrt{5}}}[/tex]
In the given mathematical expression, fractions containing square roots are known as surds. They are usually no longer further simplified but they can be converted to decimal numbers with the use of calculators. Surds are commonly known as irrational numbers.
From the given expression, we are going to convert it to decimal numbers to determine the options that correspond to it.
[tex]\mathbf{\dfrac{7}{\sqrt{5}} = 3.1305}[/tex]
From the given options:
[tex]\mathbf{\dfrac{7 \sqrt{5}}{25} = 0.6261 }[/tex]
[tex]\mathbf{35 \sqrt{5} = 78.26}[/tex]
[tex]\mathbf{\dfrac{49}{\sqrt{35}} = 8.2825}[/tex]
[tex]\mathbf{\dfrac{7\sqrt{5}}{5} = 3.1305}[/tex]
Therefore, from the above solution, the fourth option correctly corresponds and is equal to the expression 7/√5
Learn more about surds here:
https://brainly.com/question/24436961?referrer=searchResults
20 points if right.
Answers:
A. continuous data, graph B
B. discrete data, graph B
C. discrete data, graph A
D. continuous data, graph A
The answer is option A
I'm not sure how to get the answer can you help me?
Suppose △PKN≅△BGH.
Which other congruency statements are correct?
Select each correct answer.
A △NKP≅△HBG
B △KPN≅△BHG
C △NPK≅△HBG
D △KNP≅△GHB
C and D are correct. Look how the letters correspond to each other.
Ira writes that the sum of a+b is a number that is located a distance of [b] units from a on the number line. Choose four values for a and b and show that this is true. Use the four number lines on the right to show your work and support your answer
Answer:
1. Take a=4, b=6
a+b
=4+6
=10( Both are positive integers)
2. a=4 , b= -6
then 4 + (- 6)
= 4 - 6
= -2 [Smaller is positive integer and larger is negative integer , So subtract smaller from larger and apply the sign possessed by larger integer]
3. a = -4, b= -6
a+ b
= -4 -6
=-10 [ Both are negative integers add them apply - sign before the number.]
4. a = -4, b=6
a +b
= -4+ 6
= 2 [one is positive and other is negative subtract smaller from larger and apply positive sign before the number.]
what is the radius of a circle with circumference 56 in?
the radius is 8.917197452 in
Your total restaurant bill for food and drinks is $63.57. What is a good estimated cost for just the food and drinks
To estimate the cost of just the food and drinks, subtract the cost of other items from the total bill.
Explanation:To estimate the cost of just the food and drinks, we need to subtract the cost of other items from the total bill. If we assume that the bill includes a fixed cost of $25 for other items such as taxes and service charges, we can subtract this amount from the total bill to get an estimate for just the food and drinks. So, the estimated cost for just the food and drinks would be $63.57 - $25 = $38.57.
Learn more about Estimating cost here:https://brainly.com/question/33486084
#SPJ12
The estimated cost for just the food and drinks is $63.57.
Explanation:To find the estimated cost for just the food and drinks, you need to subtract any other expenses from the total bill.
For example, if there were additional charges for tax, service fees, or tips included in the total bill, you would subtract those amounts.
Let's assume there are no additional charges, so the estimated cost for just the food and drinks would be equal to the total bill amount of $63.57.
Learn more about estimated cost here:https://brainly.com/question/33486084
#SPJ12
Factor the expression completely over the complex numbers.
x^4 + 10x^2 + 25
Enter your answer in the box.
Answer:
Step-by-step explanation:
I would say
(x+5)(x-5)(x+5i)(x-5i)
The factor of the expression x⁴ + 10x² + 25 is (x + √5i)(x - √5i) after using the factor method.
What is a complex number?It is defined as the number which can be written as x+iy where x is the real number or real part of the complex number and y is the imaginary part of the complex number and i is the iota which is nothing but a square root of -1.
It is given that:
The expression is:
= x⁴ + 10x² + 25
Let t = x²
= t² + 10t + 25
= (t + 5)²
= (x² + 5)²
x² = -5
x = ±√5i
(x + √5i)(x - √5i)
Thus, the factor of the expression x⁴ + 10x² + 25 is (x + √5i)(x - √5i) after using the factor method.
Learn more about the complex number here:
brainly.com/question/10251853
#SPJ2
Danny poured 78 liters of water into containers x, y, and z. The ratio of the volume of water in container x to the volume of water in container y is 5:2. The ratio of the volume of water in container y to the volume of water in container z is 8:11.
a) how much water was poured into container s?
b) how much more water was poured into container x than container z?
a) Container z: 22 liters. b) Container x has 18 liters more than container z.
To solve this problem, let's first find the volumes of water in containers x, y, and z.
Let's represent the volume of water in container x as 5x liters and the volume of water in container y as 2x liters, based on the ratio given.
Then, according to the ratio of y to z, if the volume of water in container y is 2x, the volume of water in container z is (11/8) × 2x liters.
Now, we can set up an equation to find the value of x.
5x (container x) + 2x (container y) + (11/8 × 2x) (container z) = 78 liters
5x + 2x + (11/8 × 2x) = 78
5x + 2x + (11/4 × x) = 78
Multiplying through by 4 to clear the fraction:
20x + 8x + 11x = 312
39x = 312
x = 312 / 39
x = 8
Now, we can find the volumes of water in each container:
Container x = 5x = 5 × 8 = 40 liters
Container y = 2x = 2 × 8 = 16 liters
Container z = (11/8) × 2x = (11/8) × 16 = 22 liters
a) The amount of water poured into container s (assuming it was meant instead of "s" since "s" wasn't mentioned in the problem) is the volume of water in container z, which is 22 liters.
b) The difference in the amount of water poured into containers x and z:
Volume in container x - Volume in container z = 40 liters - 22 liters = 18 liters.
So, 22 liters of water was poured into container s, and 18 liters more water was poured into container x than into container z.
-9 - 4b = 3 + 8b how do you solve this?
Have all the terms containing the variable on one side of the equation and the rest of the terms on the other side of the equation.
I will put all terms containing the variable b on the left side of the equation and the rest on the right side of the equation.
Subtract 8b from both sides of the equation.
-9 -12b = 3
Add 9 to both sides of the equation to isolate the term with the variable b.
-12b = 12
Divide both sides of the equation by -12 to solve for b.
b = -1
The hottest temperature recorder in the world and degrees fahrenheit can be found by multiplying 13.46 x 10 finest temperature justify your pod seizur the hottest temperature recorded in the world and degrees fahrenheit can be found by multiplying 13.46 x 10 finest temperature justify your producer
The hottest temperature ever recorded on Earth was 134°F in Death Valley, California. If you were to multiply this temperature by 13.46, then the result would not provide a realistic temperature on Earth. This is due to the non-linear relationship of Fahrenheit or any temperature scale with its multiples.
Explanation:The question seems to be asking whether, if the hottest recorded temperature in the world in degrees Fahrenheit is multiplied by 13.46, the result would be equal to ten times that same temperature. This arithmetic operation would not, in reality, be accurate in defining the world's hottest temperature. This is because Fahrenheit temperatures don't have a linear relationship with its multiples. For example, if the highest recorded temperature is 120°F, 10 times that would be 1200 and this temperature is not realistic on earth.
The hottest temperature ever recorded on Earth was 134°F (56.7°C) in Furnace Creek Ranch, Death Valley, California, USA on July 10, 1913. This temperature was recorded using a standard thermometer in a ventilated, shaded structure 1.5 meters above the ground, which is the standard method for measuring ambient temperature. Doubling or multiplying this figure as suggested wouldn't produce a viable result in real-world physics or climatology.
Learn more about hottest temperature here:https://brainly.com/question/33560203
#SPJ2
What is the result of dividing x^3−7 by x + 2?
x^2−2x+4− 15/x+2
x^2−2x+4− 1/x+2
x^2−2x+4+ 1/x+2
x^2−2x+4+ 15/x+2
Answer:
Choice A: x^2−2x+4− 15/x+2
Step-by-step explanation:
The result of the division of the cubic polynomial x^3-7 by the binomial [tex]x+2 is x^2-2x+4 - 15/(x+2)[/tex], as obtained by carrying out the process of polynomial division.
Explanation:The student is asking for the result of dividing a cubic polynomial, x^3-7, by a binomial, x+2. To do this, we need to perform polynomial division. The result of this division is [tex]x^2-2x+4 - 15/(x+2)[/tex]. We get this by setting up and performing the division, which operates similarly to long division, except that you are working with polynomials instead of numbers. The steps involved are too complicated to list here, but involve repeatedly subtracting multiples of x+2 from x^3-7 until the remainder is less than x+2, at which point you can't subtract more multiples of x+2.
Learn more about Polynomial division here:https://brainly.com/question/36507743
#SPJ3